PENGARUH PROFITABILITAS, LEVERAGE, DAN FIRM SIZE TERHADAP TAX AVOIDANCE - Gibrillia, Audi; Sudirgo, Tony (Jurnal Paradigma Akuntansi, 2023)
The main purpose of this research is to determine whether there is an influence between profitability, leverage and firm size on tax avoidance on listed manufacturing companies in Indonesia Stock Exchange (IDX). The sample of this study used a purposive sampling method and started from the 2018-2020 period by utilizing 210 data consisting of 70 companies engaged in manufacturing. The data processing technique using multiple regression analysis and assisted by the software program used in this study to process the data is Eviews 12. The results of this study indicate that profitability has a negative effect on tax avoidance, while leverage has a positive effect on tax avoidance. While the size of the company has no effect on tax avoidance.